Isolation-Induced Ultrasonic Vocalization in Environmental and Genetic Mice Models of Autism - Shekel, Itay; Giladi, Shaked; Raykin, Eynav; Weiner, May; Chalifa-Caspi, Vered; Lederman, Dror; Kofman, Ora; Golan, Hava M. (Frontiers in Neuroscience, 2021)
Studies in rodent models suggest that calls emitted by isolated pups serve as an early behavioral manifestation of communication deficits and autistic like behavior. Previous studies in our labs showed that gestational exposure to the pesticide chlorpyrifos (CPF) and the Mthfr-knock-out mice are associated with impaired social preference and restricted or repetitive behavior. To extend these studies, we examine how pup communication via ultrasonic vocalizations is altered in these ASD models. We implemented an unsupervised method of hierarchical clustering based on the spectral properties of the syllables in order to exploit syllable classification to homogeneous categories while avoiding over-categorization. Comparative exploration of the spectral and temporal aspects of syllables emitted by pups in two ASD models point to 1) Most clusters showed a significant effect of the ASD factor on the start frequency and bandwidth and 2) The highest percent change due to the ASD factor was on the bandwidth and duration. In addition, we found sex differences in the spectral and temporal properties of the calls in both control groups as well as an interaction between sex and the gene/environment factor. Considering the basal differences in the characteristics of syllables emitted by pups of the C57Bl/6 and Balb/c strains used as a background in the two models, we suggest that the above spectral-temporal parameters: start frequency, bandwidth and duration are the most sensitive to the developmental changes in brain circuitry in ASD models.